Relationship between lifetime under creep and constant stress rate for polymer-matrix composites - R. M. Guedes (2009)
The present article reviews two existing theoretical approaches for creep failure criteria of viscoelastic materials. One criterion is based on the continuum damage mechanics (CDM) and the other is based on the fracture mechanics extended to viscoelastic materials. Although both theoretical frameworks are based on different physical concepts, the deduced lifetime expressions turn out to be equivalent even though its parameters have different physical interpretation. It is proved that both theoretical frameworks, when extended to variable stress loading cases, imply the linear cumulative damage (LCD) law. Additionally the relationship obtained between the creep-rupture and constant stress rate until failure is very simple. Moreover this simple relationship is obtained independently by two different cumulative damage laws, which do not obey the LCD law, and by experimental evidence using published data for two different polymer-matrix composites (PMC). Finally a micromechanical model, used for creep-rupture of unidirectional composites, is extended for constant stress rate until failure to corroborate the simple relationship obtained between the creep-rupture and constant stress rate until failure.